What's in it for me? Self-interest and preferences for distribution of costs and benefits of energy efficiency policies - Valeria Fanghella; Corinne Faure; Marie-Charlotte Guetlein; Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
Public acceptability appears an essential condition for the success of lowcarbon transition policies. In this paper, we investigate the role of self-interest on citizens' preferences for the distribution of costs and of environmental benefits of energy efficiency policies. Using a discrete choice experiment on nationally representative household samples of Italy, Sweden, and the United Kingdom, we first investigate preferences for specific burden-sharing rules and for the distribution of policy environmental benefits accruing primarily in rural and/or urban areas. We examine the role of self-interest in a correlation manner by looking at the effects of income and of location of residency on preferences for these policy attributes. Moreover, we investigate the effect of self-interest on preferences for burden-sharing rules in a causal manner by exogenously priming subsets of participants to feel either rich or poor. Our results suggest that the polluter-pays rule is the most popular burden-sharing rule and an equalamount rule the least popular and that policies with environmental benefits accruing primarily in rural areas are less preferred, with some heterogeneity in preferences across the three countries. We also find evidence for self-interest, both through correlational and through causal approaches.
urn:nbn:de:0011-n-6439631
Keywords: 330; policy acceptability; self-interest; distributional fairness; discretechoice experiment; energy efficiency